Improvement of Soybean Crop for Yield, Stress Tolerance, and Value-Added Products Using a Transgenic Approach - Deepak B. Shelke; Mahadev R. Chambhare; Ganesh C. Nikalje; T. D. Nikam (Advances in Agriculture)
Soybean (Glycine max) is an economically important crop, ranking first among the edible oilseed crops in the world due to its oil content and nutritional value. Besides, it is used as a dietary supplement and a source of pharmaceuticals. The recent rapid climate changes and increasing global population have led to increasing demand for vegetable oil. In the recent past, advances in the field of plant biotechnology have revolutionized agricultural practices at a global level to enhance the yield of crops. This technology not only makes an impact on the agricultural market but also opens up new corridors for agriculture-related industrial applications of this important crop. Therefore, in the last two decades, soybean has gained attention for genetic improvement with remarkable developments in the manipulations of genes for the induction of desired characteristics. In this review, we introduced the transgenic approach as a promising tool for the improvement of soybean oilseed quality and productivity. Then, the enhancement of nutritional and pharmaceutical value together with biotic and abiotic stress-resistant ability was summarized and compared. The methods and strategies for achieving soybean crops with improved abiotic stress tolerance, productivity, and pharmaceutics are categorized to help with future research.